Accommodation and acceptance : an exploration in interfaith relations - Mong, Ambrose Ih-Ren, 1959- (James Clarke & Co, 2015)
A study of the relations between Christianity and the other major religions of Asia, delving into the diverse theologies of those who pioneered interfaith dialogue and acceptance. As Hans Küng said, "No peace among the nations without peace among the religions. No peace among the religions without dialogue between the religions. No dialogue between the religions without investigation of the foundations of the religions." Accommodation and Acceptance is a crucial work in both promoting interreligious dialogue and exploring the turbulent history of Christian faith and identity in Asia down the years. From the reaction to missions, often inextricably linked with the practice of colonialism, to the rise of religious pluralism, Ambrose Mong examines the relationships between the leading faiths of Asia up to the present day. Whether practicing pluralism or exclusivism, the history of Christianity in Asia is long and fascinating. Ambrose Mong delves into the biography of intercultural pioneers like Matteo Ricci and Timothy Richard to understand better the theology--as well as the pragmatism-- behind cultural accommodation, and the necessary mutability of an eternal church. (Publisher).